Alterations of the autoimmune regulator transcription factor and failure of central tolerance: APECED as a model. (January 2013) - Gallo, Vera; Giardino, Giuliana; Capalbo, Donatella; Palamaro, Loredana; Romano, Rosa; Santamaria, Francesca; Maio, Filomena; Salerno, Mariacarolina; Vajro, Pietro; Pignata, Claudio
Self–nonself discrimination plays a key role in inducing a productive immunity and in preventing autoimmune reactions. Central tolerance within the thymus and peripheral tolerance in peripheral lymphoid organs lead to immunologic nonresponsiveness against self-components. The central tolerance represents the mechanism by which T cells binding with high avidity to self-antigens are eliminated through the so-called negative selection. Thymic medullary epithelial cells and medullary dendritic cells play a key role in this process, through the expression of a large number of tissue-specific self-antigens involving the transcription factor autoimmune regulator (AIRE). Mutations of AIRE result in autoimmune polyendocrinopathy candidiasis ectodermal dystrophy, a rare autosomal recessive disease (OMIM 240300), which is the paradigm of a genetically determined failure of central tolerance and autoimmunity. This review focuses on recent advances in the molecular mechanisms of central tolerance, their alterations and clinical implication.